Internet Marketing: Konsep dan Persoalan Baru Dunia Pemasaran - Bertha Silvia Sutejo (Jurnal Manajemen Maranatha, 2006)
With increased globalization of the world economies, for most enterprises, market opportunities seem to be endless these days. Consequently, departing from the traditional commercial strategies and tactics, innovative managers are looking for unique ways to compete more effectively on a local, regional and global basis. Internet has received so much attention from business world because the internet will accelerate the decrease in costs of information. In addition, it provides a universal availability and higher quality of information. Internet also provides a fundamentally different environment for international marketing and requires a different approach. Marketing mix on internet marketing consist of five P’s: price, product, promotion, place, and personalization. Internet marketing establishes the new marketing paradigm. This paper will try to explain the effect of internet marketing on marketing mix and to determine some building blocks in the new marketing paradigm.